Off worlding autonomy: Provincial infrastructure and orbital sovereignty in the Ford-Starlink partnership - Sharp, Rory Zane Rafferty; Weizman, Aviva (AoIR Selected Papers of Internet Research, 2026)
This paper presents the results of an ongoing research project assessing a deal between Ontario Premier Doug Ford and Elon Musk’s Starlink to provide wireless internet service to isolated communities in northern Ontario with Starlink satellites. We ask how the Ford-Starlink partnership is situated within Canadian histories of provincial autonomy and Indigenous campaigns for political recognition and infrastructural inclusion while exploring what the deal can tell us about the relationship between local governance and technologically mediated transnational capital. Using mixed methods and digital tools, including AntConc and Factiva, we review provincial and federal infrastructure policy alongside media coverage to show how the Ford government instrumentalizes ongoing campaigns to expand wireless internet access to historically excluded Indigenous communities. In the guise of an idealized private-public partnership, the Ford-Starlink partnership demonstrates that provincial authority is adjusting to a new political calculus that circumvents conventional models of national sovereignty through investment in non-terrestrial networks (NTNs). This project is uniquely suited to AOIR’s 2025 theme. While far from ubiquitous, NTNs pose profound challenges. High investment costs and historical access to space programmes stand to constrain the development of NTNs, further concentrating capital and control in the Global North. Though an acute problem for the Global South, the Canadian context offers an insightful example of how these trajectories converge. We draw on Indigenous studies of infrastructure and inclusion, research on wireless media infrastructures, and ongoing debates about the evolution of neoliberalism to highlight how NTNs enclose claims to infrastructural autonomy and national sovereignty.